Suboptimal Inhibition of Platelet Cyclooxygenase 1 by Aspirin in Systemic Lupus Erythematosus: Association With Metabolic Syndrome1. Issue 2 (February 2014) - Kawai, Vivian K.; Avalos, Ingrid; Oeser, Annette; Oates, John A.; Milne, Ginger L.; Solus, Joseph F.; Chung, Cecilia P.; Stein, C. Michael
<x xml:space="preserve">Abstract</x> Objective Low‐dose aspirin prevents platelet aggregation by suppressing thromboxane A2 (TXA2) synthesis. However, in some individuals TXA2 suppression by aspirin is impaired, indicating suboptimal inhibition of platelet cyclooxygenase 1 (COX‐1) by aspirin. Because patients with systemic lupus erythematosus (SLE) have increased risk of thrombotic events, many receive aspirin; however, the efficacy of aspirin in SLE has not been determined. We examined the hypothesis that aspirin response is impaired in SLE. Methods We assessed the effect of aspirin by measuring concentrations of the stable metabolite of TXA2, serum thromboxane B2 (sTXB2), before and after treatment with daily aspirin (81 mg) for 7 days in 34 patients with SLE and 36 control subjects. The inability to suppress sTXB2 synthesis to <10 ng/ml represents suboptimal inhibition of platelet COX‐1 by aspirin. Results Aspirin almost completely suppressed sTXB2 in control subjects to median 1.5 ng/ml (interquartile range [IQR] 0.8–2.7) but had less effect in patients with SLE (median 3.1 ng/ml [IQR 2.2–5.3]) (P = 0.002). A suboptimal effect of aspirin was present in 15% (5 of 34) of the patients with SLE but not in control subjects (0 of 36) (P = 0.023). Incomplete responders were more likely to have metabolic syndrome (P = 0.048), obesity (P = 0.048), and higher concentrations of C‐reactive protein (CRP) (P = 0.018). Conclusion The pharmacologic effect of aspirin is suboptimal in 15% of patients with SLE but in none of the control subjects, and the suboptimal response was associated with metabolic syndrome, obesity, and higher CRP concentrations.